1991
DOI: 10.1002/bbpc.19910950208
|View full text |Cite
|
Sign up to set email alerts
|

Shear Induced Micellar Structures

Abstract: Mixed solutions of the anionic surfactant Sodiumdodecylsulfate (SDS) and the zwitterionic Tetradecyldimethylaminoxid (TDMAO) were studied under shear in a Couette‐type apparatus. For shear rates exceeding a critical shear gradient γc the solutions show birefringence which approaches a constant value ΔnMAX with increasing shear rate. At the same time properties like the shear viscosity and the normal stress difference increase dramatically. A structural modification must thus have taken place for γ > γc: a shea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
98
0
1

Year Published

1992
1992
2003
2003

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 95 publications
(106 citation statements)
references
References 24 publications
7
98
0
1
Order By: Relevance
“…This behavior is reminiscent of observations in multiphase fluids (16) and of elastic instabilities in couette flow of certain polymer solutions (17,18). The former effects, ascribed to tumbling of the director in liquid crystal fluids, are in keeping with the view of liquid crystal domains in SIS (11,12), the latter effects with long polymer-like surfactant aggregates (13). Stable oscillations, however, require periodically changing processes, such as build-up and destruction of SIS, that are concerted in the entire volume investigated.…”
Section: Discussionmentioning
confidence: 67%
“…This behavior is reminiscent of observations in multiphase fluids (16) and of elastic instabilities in couette flow of certain polymer solutions (17,18). The former effects, ascribed to tumbling of the director in liquid crystal fluids, are in keeping with the view of liquid crystal domains in SIS (11,12), the latter effects with long polymer-like surfactant aggregates (13). Stable oscillations, however, require periodically changing processes, such as build-up and destruction of SIS, that are concerted in the entire volume investigated.…”
Section: Discussionmentioning
confidence: 67%
“…More recently, rheo-optical techniques were applied with success to the study of wormlike micelles [2,14,117,161,[169][170][171][172]. Experimental set-ups designed for studying complex fluids generally utilize a Couette cell as a shearing device (Figure 14).…”
Section: Flow Birefringencementioning
confidence: 99%
“…The vector u(s) is tangent to the micellar axis and s denotes the curvilinear length. The bending free energy per unit of s is proportional to the product κC 2 , where κ is the bending modulus of the chain and C its curvature. For surfactants, Ben-Shaul and coworkers have shown that this free energy has a molecular origin [95].…”
Section: Persistence Lengthmentioning
confidence: 99%
See 2 more Smart Citations